PENGEMBANGAN SISTEM PEMANTAUAN CERDAS KINERJA PENGAWAS SEKOLAH - FAUZAN AKHMAD MAHANANI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The performance of school supervisors in carrying out academic and managerial supervisory duties in education units which includes the preparation of supervision programs, implementation of guidance, monitoring of the implementation of National Education Standards, assessment, mentoring is very important in maintaining and improving the quality of education. The purpose of this study was to determine the stages of developing an information system for monitoring the performance of school supervisors based on information technology at the Department of Youth and Sports Education, Banjarnegara Regency. The information system developed was named “Sipedas” which is an acronym for sistem Informasi pemantauan cerdas. The research method used in this research is the Research and Development (R&D) method. In the analysis combines qualitative and quantitative data to find out how much the utilization of the Sipedas information system is used. The average usability test results of Sipedas show more than 72% of user respondents' answers stating that Sipedas is